Neuroprotective Effects of the Anti-cancer Drug Lapatinib Against Epileptic Seizures via Suppressing Glutathione Peroxidase 4-Dependent Ferroptosis - Jia, Ji-Ning; Yin, Xi-Xi; Li, Qin; Guan, Qi-Wen; Yang, Nan; Chen, Kang-Ni; Zhou, Hong-Hao; Mao, Xiao-Yuan (Frontiers in Pharmacology, 2020)
Epilepsy is a complex neurological disorder characterized by recurrent and unprovoked seizures. Neuronal death process is implicated in the development of repetitive epileptic seizures. Therefore, cell death can be harnessed for ceasing seizures and epileptogenesis. Oxidative stress is regarded as a contributing factor of neuronal death activation and there is compelling evidence supporting antioxidants hold promise in abrogating seizure-related cell modality. Lapatinib, a well-known anti-cancer drug, has been traditionally reported to exert anti-tumor effect via modulating oxidative stress and a recent work illustrates the improvement of encephalomyelitis in rodent models after lapatinib treatment. However, whether lapatinib is beneficial for inhibiting neuronal death and epileptic seizure remains unknown. Here, we found that lapatinib remarkably prevented kainic acid (KA)-epileptic seizures in mice and ferroptosis, a newly defined cell death which is associated with oxidative stress, was involved in the neuroprotection of lapatinib. In the ferroptotic cell death model, lapatinib exerted neuroprotection via restoring glutathione peroxidase 4 (GPX4). Treatment with GPX4 inhibitor ras-selective lethal small molecule 3 (RSL3) abrogated its anti-ferroptotic potential. In a mouse model of KA-triggered seizure, it was also validated that lapatinib blocked GPX4-dependent ferroptosis. It is concluded that lapatinib has neuroprotective potential against epileptic seizures via suppressing GPX4-mediated ferroptosis.